2019
DOI: 10.1097/acm.0000000000002686
|View full text |Cite
|
Sign up to set email alerts
|

Competency-Based Curriculum Development to Meet the Needs of People With Disabilities: A Call to Action

Abstract: People with disabilities constitute 22.2% of the population in the United States, and virtually all physicians have people with disabilities in their clinical practice across a wide range of diagnostic groups. However, studies demonstrate that people with disabilities are inadequately served by the health care system, leading to high costs and poor outcomes. The authors argue that one cause of this discrepancy is that medical students receive limited training in the care of people with disabilities and may the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 48 publications
0
87
0
Order By: Relevance
“…When generalizing this data to all American medical schools, the authors suggest that potentially no more than 23% have disability-focused training [46]. Among these schools, varying degrees of disability-related training have been implemented, including hands-on experiences with standardized patients, simulation exercises, panel discussions with patients with disabilities, and didactic approaches to highlight disability-related issues [46][47][48][49]. Of note, no standardized curriculum has been widely adopted.…”
Section: Disability Competence In Education and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…When generalizing this data to all American medical schools, the authors suggest that potentially no more than 23% have disability-focused training [46]. Among these schools, varying degrees of disability-related training have been implemented, including hands-on experiences with standardized patients, simulation exercises, panel discussions with patients with disabilities, and didactic approaches to highlight disability-related issues [46][47][48][49]. Of note, no standardized curriculum has been widely adopted.…”
Section: Disability Competence In Education and Trainingmentioning
confidence: 99%
“…Of disability curricula that have been proposed [8,[46][47][48][49][50][51][52][53], several follow the Bloom's taxonomy framework used widely throughout healthcare education, propos-ing instruction based on three educational outcomes: knowledge, skills, and attitudes [49,[51][52][53]. "Knowledge" and "skills" related to disability are largely addressed in cultural competence training, often alongside but discrete from issues related to race, gender, and class [49].…”
Section: Disability Competence In Education and Trainingmentioning
confidence: 99%
“…Using a multimodal form of education including didactic sessions to introduce basic concepts (example: health disparities, cultural competency vs. humility, othering) and definitions (example, different types of disabilities and their respective accommodations), implicit bias testing, hands-on simulation scenarios, research opportunities, and community-based experiences allows for full integration. 67,68 We also suggest modification of some of the core ACGME EM milestones to reflect the integration of diversity and inclusion curricula, specifically incorporating milestones that evaluate residents on care of the patient with a disability. Examples of the original ACGME milestones can be seen in Figures 3A through 3C, 69 followed by suggested language modification.…”
Section: Recommendations For Em Residency Curriculum Design Curriculamentioning
confidence: 99%
“…In undergraduate medical education, it has been demonstrated that incorporating individuals from the community with disabilities into training on caring for patients with disabilities had a positive effect on the self-reported comfort levels of young learners in caring for these patients. 37,68 Additionally, the incorporation of narratives from the "expert by experience" has the potential to positively influence one's perspective of those with disabilities. 70 Outside of the field of medicine, research has shown that learning from a person with a disability is more beneficial not only to others with disabilities, but also to those without disabilities.…”
Section: Engage the Disability Community In Residency Educationmentioning
confidence: 99%
See 1 more Smart Citation